Types of Hedges Used by American and Vietnamese Celebrity - Ngoan, Nguyen Quang; Quyen, Nguyen Le To (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract: The study was to compare and contrast type of hedges used by American and Vietnamese celebrities in responses to questions in interviews. The data were collected from 96 online interviews with American and Vietnamese celebrities. The study was conducted mainly with quantitative methods with the combination of some qualitative methods for explanation and discussion. The findings showed that out of the five categories under investigation, “Quality hedges” were most frequently-used with a rather high rate, while “Relevance hedges” took the lowest position in frequency by both groups of celebrities. Also, hedges used in the American and Vietnamese data were different from each other in the distribution of “Quantity hedges”, “Manner hedges” and “Mixed hedges” . Keywords: American celebrities (Acels), Vietnamese celebrities (Vcels), hedges on quality maxim (QlHs), hedges on quantity maxim (QnHs), hedges on relevance maxim (ReHs), hedges on manner maxim (MaHs), mixed hedges (MiHs).